Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1088/0957-4484/25/26/265301
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nanosecond and femtosecond pulsed laser deposition of silver nanoparticle films

Abstract: Nanoparticle (NP) films of silver were prepared using nanosecond (ns) and femtosecond (fs) pulsed laser deposition (PLD) in vacuum. The flux and energy distribution of the ions in the plasma part of the ablation plume were measured using a Langmuir ion probe. The deposition energy efficiencies of ns and fs silver PLD were also compared. For equivalent thickness up to ∼3 nm the NPs made by ns-PLD are well separated and roughly circular, but for higher thicknesses the NPs begin to coalesce. For equivalent thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 41 publications
(45 reference statements)
1
17
0
Order By: Relevance
“…Generally speaking, nanoparticles are formed in the first stages of laser ablation process either by a direct ejection from the target (typically in the case of subpicosecond laser pulses) or during the expansion of the ablated species in a background atmosphere. Different theoretical models describing the synthesis of nanoparticles have been proposed [38][39][40][41]; remarkably, it has been shown that the generation of nanoparticles represents a general feature of laser ablation and it is not limited to specific materials or deposition regimes [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, nanoparticles are formed in the first stages of laser ablation process either by a direct ejection from the target (typically in the case of subpicosecond laser pulses) or during the expansion of the ablated species in a background atmosphere. Different theoretical models describing the synthesis of nanoparticles have been proposed [38][39][40][41]; remarkably, it has been shown that the generation of nanoparticles represents a general feature of laser ablation and it is not limited to specific materials or deposition regimes [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] From several decades, it has largely been used for research and is considered a true versatile technique for thin-film deposition of a variety of materials including noble metals. [1][2][3][4][5][6][7][8][9][10] Instead, PLD has not become a standard coating technology to incorporate for industrial application; roughcasting the same problems, it had 20 years back. There are constrains that limit the use of classical PLD for industrial-scale application such as high vacuum requirements, slow deposition, limited area deposition, issues with the coating of irregular objects, and longer deposition time.…”
Section: Introductionmentioning
confidence: 99%
“…The transition from classical vacuum PLD into APLD is appealing since it reduces cost and opens the possibility of fabrication of thin solid films in an industrially feasible environment. This gas‐phase synthesis method of nanomaterials involving laser ablation of solid precursors is relatively simple, in the sense that it allows direct vaporization of the bulk target material with full stoichiometric control 1‐6 . From several decades, it has largely been used for research and is considered a true versatile technique for thin‐film deposition of a variety of materials including noble metals 1‐10 .…”
Section: Introductionmentioning
confidence: 99%
“…From a diagnostic perspective several papers have reported on the behavior of LP in transient plasma generated by short or ultrashort laser ablation of Ag in various con gurations in terms of laser properties 20,21 , gas nature [22][23][24][25][26] and LP geometries 8,23,27,28 . The general consensus is that during the ablation process there are generated high energy multiple charged ions 9,14,20 (up to 100 eV), and complex nanostructures 20,22 that can affect the properties of the thin lms. Several studies have been focused on the angular distribution of Ag ions and the deposited material showing the dependence on the laser uence and gas nature with a widening of the ionic distribution seen with the increase of the background pressure 29 .…”
Section: Introductionmentioning
confidence: 99%
“…A particular interest has been given to laser-produced Ag plasma as Ag has shown promising results in a wide range of applications spanning from plasmonic resonance 17 , exible conductive electrodes 18 or even medical and biological applications 19 . From a diagnostic perspective several papers have reported on the behavior of LP in transient plasma generated by short or ultrashort laser ablation of Ag in various con gurations in terms of laser properties 20,21 , gas nature [22][23][24][25][26] and LP geometries 8,23,27,28 . The general consensus is that during the ablation process there are generated high energy multiple charged ions 9,14,20 (up to 100 eV), and complex nanostructures 20,22 that can affect the properties of the thin lms.…”
Section: Introductionmentioning
confidence: 99%